Phytochemical Screening And Evaluation Of Antimicrobial Activities Of In Vitro And In Vivo Grown Plant Extracts Of Lobelia Inflata L. - NAGANANDA G.S; AARTHI KRISHNAMOORTHY; ARIJIT DAS; SOURAV BHATTACHARYA (International Journal of Pharma and Bio Sciences, 2012)
Lobelia inflata L. is a medicinally important herb used in the treatment of respiratory problems. The objectives of this present study were phytochemical screening and evaluation of antimicrobial activities of aqueous, ethanolic and methanolic extracts of different parts of the plant such as leaf, root, stem and inflorescence. Extracts of in vitro grown callus of the leaf, obtained after 4 weeks of incubation on 1X MS medium containing 1mg/ml 2, 4-D and 1mg/ml Kinetin were also screened. Fifteen extracts revealed the presence of phytochemicals such as alkaloids, carbohydrates and phytosterols. The methonolic extracts of root showed alkaloid (0.50 mg/ml) and stem showed carbohydrate (1.76 mg/ml). The ethanolic leaf extract showed phytosterols (3.68 mg/ml). Antimicrobial activities revealed that among all the extracts, the highest sensitivity was recorded for the methanolic and ethanolic extract of inflorescence against Klebsiella pneumonia and Staphylococcus aureus respectively. The ethanolic extract of root and stem showed the highest zone of inhibition against Serratia marcescens. None of the aqueous extracts exhibited any antimicrobial activity. The methanolic extract of the callus was found to inhibit Cryptococcus neoformans among the various fungal pathogens. This study may provide the scientific basis for the use of this plant for various therapeutic purposes. .